(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
This article presents data on autumn monitoring of mammals distributed in the territory of the "Southern Ustyurt" National Nature Park in 2021-2024. Research work was carried out on the basis of generally accepted bioecological methods in the vicinity of Lake Sarykamysh, in the Kulan-Takyr, KaplanKyr, and Asseke-Audan depressions of Southern Ustyurt. As a result of the research, 14 species of mammals were identified. Eight of them are species listed in the Red Book of Uzbekistan